A review of pursuit and saccadic eye movements and their utility in stroke - Fracica, Elizabeth; Hale, David E.; Gold, Daniel R. (Frontiers in Stroke, 2023)
The Head Impulse-Nystagmus-Test of Skew (+ Hearing) or HINTS+ exam is a well-established clinical bedside test used in evaluating whether patients with the acute vestibular syndrome have features concerning for a central etiology (e.g. stroke). There are other components of the ocular motor exam which are helpful in the acute setting including smooth pursuit and saccades. We will discuss the anatomy and physiology of the saccade and smooth pursuit pathways from cortex to infratentorium in the context of anterior and posterior circulation strokes in general, but with a particular emphasis on distinct vestibular stroke syndromes. For each stroke localization, we review the vascular supply, the expected findings on the HINTS+ exam and correlate this with expected findings on the smooth pursuit and saccade exams to aid in bedside diagnosis.